Elucidating the elusive crystal structure of 2, 4, 6-tris(2-pyrimidyl)-1, 3, 5-triazine1. Issue 10 (14th March 2015) - Safin, Damir A.; Tumanov, Nikolay A.; Leitch, Alicea A.; Brusso, Jaclyn L.; Filinchuk, Yaroslav; Murugesu, Muralee
<x xml:space="preserve">Abstract</x> 2, 4, 6-Tris(2-pyrimidyl)-1, 3, 5-triazine has been synthesized using two approaches: via trimerization of 2-cyanopyrimidine at 160 °C and by the reaction of 2-cyanopyrimidine with pyrimidine-2-carboximidamide.